La desnaturalizacion del delito de estafa por parte del denunciante, previa la existencia de un proceso ejecutivo, en el Cantón San Miguel de Bolivar, periodo 2021 - Lara Naranjo, Wilber Patricio (2023)
Within Ecuadorian legislation, the criminal law regulates illegal conduct that is prosecuted in crimes of fraud, considering this crime, when a person in order to obtain a patrimonial benefit for himself, or for other people, simulating false facts, to mislead, harming your assets. However, many people confuse the crime of fraud with a civil process (money loan), and at the moment of not being able to collect through executive channels, through poor legal advice, they report to the Prosecutor's Office, distorting the crime, causing a loss of state resources. In this investigation, the objective is to establish the legal effects of the crime of fraud and how these are prosecuted in the Prosecutor's Office of the San Miguel de Bolívar canton, for compliance with this, a qualitative methodology was used, in order to analyze the criteria under which to act. justice operators (prosecutors and judges) in fraud cases, in the same way the corresponding bibliography has been reviewed that allows to know about the subject, in order to determine the respective conclusions. Legal professionals must be objective when advising their clients, when filing a complaint with the prosecution. Keywords: Illegal conduct, crime, legal effects, fraud, assets, enforcemen